Metabolic Dysfunction-associated Steatotic Liver Disease Alters Fatty Acid Profiles in the Liver and Adipose Tissue - Palomurto, Saana; Virtanen, Kirsi A.; Karja, Vesa; Schwab, Ursula; Kaminska, Dorota; Kakela, Pirjo; Pihlajamäki, Jussi; Männistö, Ville (The Endocrine Society, 2026)
Context: The alterations in systemic fatty acid (FA) metabolism in metabolic dysfunction-associated steatotic liver disease (MASLD) remain unclear.
Objective: To investigate inter-tissue crosstalk in FA metabolism in patients with MASLD, we compared FA profiles in the liver, serum, visceral, and subcutaneous adipose tissue of patients with severe obesity and normal liver, simple steatosis, or metabolic dysfunction-associated steatohepatitis (MASH).
Methods: Preoperative serum, liver, subcutaneous, and visceral adipose tissue samples were collected during laparoscopic gastric bypass surgery from 183 patients with severe obesity patients (122 women, mean age 46.9 ± 9.7 years, body mass index 43.5 ± 5.7 kg/m2). FA composition was analyzed using gas-liquid chromatography. The Kruskal-Wallis test was used to compare the FA proportions in different tissue depots.
Results: FA proportions varied more in the liver than in adipose tissue in patients with MASH. Polyunsaturated FAs (PUFA) proportions were significantly lower in the livers of patients with MASH than in those with normal livers (all adjusted P< 0.01). Conversely, dihomo-gamma-linolenic acid, adrenic acid, and arachidonic acid proportions were higher in the adipose tissues of patients with MASH (all adjusted p < 0.001).
Conclusions: Patients with MASH exhibited reduced hepatic PUFA content, increased hepatic saturated FAs, and a higher n6-to-n3 PUFA ratio, whereas no clear trends were observed in adipose tissue. These findings highlight distinct differences in FA metabolism between the liver and adipose tissue in MASLD, emphasizing tissue-specific regulatory mechanisms.